Multinational banks from developing versus developed countries: Competing in the same arena? - Petrou, Andreas (My University, 2007)
The emergence of global competitors from developing countries brought back the issue of how Multinational Enterprises (MNEs) from developing countries compete in international markets. As the small number of studies of MNEs from developing countries concentrates on manufacturing firms, this study examines service multinationals by comparing multinational banks (MNBs) from developing and developed countries. Managers' international strategic motivations were measured directly by collecting data on 112 new foreign ventures of banks worldwide. Findings suggest that both MNB groups are motivated to exploit ownership and internalization advantages. However, location motives, location choices and location entries differ which is attributed to different levels of capability. MNBs from developing countries are more likely to follow clients from home whereas MNBs from developed countries are more likely to enter developing countries in search for foreign market opportunities. These findings suggest that currently there is little overlap in international competition among these two groups of MNBs. Findings do not reflect the situation in manufacturing where some MNEs from developing countries became leading international competitors in their industries and therefore, more research should be directed in this area to understand how international service firms should compete internationally and what factors would improve competitiveness.
Keywords: Banking; Developing country; FDI; Multinational